Digital Transformation as a Mediator of the Influence of Organizational Factors and Digital Disruption on Work Unit Performance (Case Study of PT. PP Properti Tbk.) - Effendi, Muharram Aliansyah; Pasaribu, Rina Djunita (West Science Business and Management, 2025)
Digital transformation has become an imperative strategy in addressing the increasingly dynamic issues of the property business. This study endeavours to investigate the role of digital transformation as a mediator among the organizational factors (digital culture, technological infrastructure, digital leadership, digital skills) and digital disruption and their impacts on work unit performance, in a case study at PT. PP Properti Tbk. With a quantitative method and SEM-PLS analysis among 104 participants, all independent variables are found to have a significant effect on digital transformation, but only certain ones directly impact work unit performance. Digital culture, technological infrastructure, and digital skills directly and significantly affect performance, whereas digital leadership and digital disruption indirectly affect it through digital transformation. This study recommends the incorporation of digital leadership, disruption management, optimal infrastructure, and digital skills optimization as ways to maximize unit performance through digital transformation.